2023
DOI: 10.1152/japplphysiol.00287.2022
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of reduced cerebral blood flow in cerebral edema and elevated intracranial pressure

Abstract: A mechanism of elevated intracranial pressure (ICP) in cerebral edema and its effects on cerebral blood flow (CBF) are presented in this paper. To study and demonstrate these effects, a mathematical model of intracranial hydrodynamics was developed. The model simulates the intracranial hydrodynamics and the changes that occur when cerebral edema predominates. To account for an edema pathology, the model includes resistances to cerebrospinal fluid (CSF) and interstitial fluid (ISF) flows within the parenchyma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…A lumped parameter model representing interactions between brain tissue, CSF, and blood compartments was developed and described in-depth in previous articles [14,15].…”
Section: Mathematical Model Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…A lumped parameter model representing interactions between brain tissue, CSF, and blood compartments was developed and described in-depth in previous articles [14,15].…”
Section: Mathematical Model Simulationmentioning
confidence: 99%
“…However, it is observed that the point of equalization between venous pressure and intracranial pressure (ICP) shifts with the elevation of ICP. Figure 2 demonstrates the incorporation of the FCZ into our previously published model of intracranial physiology [14,15] with the FCZ component as the essential component influencing venous outflow.…”
Section: Mathematical Model Simulationmentioning
confidence: 99%